Psychological Factors Affecting EFL Students’ Speaking Performance - Ariyanti Ariyanti (Lecturer Association of Linguistics, Language Teaching, and Literature Studies in Indonesi, 2016)
Speaking has become one of important skills in learning a language especially English. Particularly, to speak in English for EFL student is not easy and need much effort to produce acceptable utterances in English. This article is aimed to investigate psychological barriers faced by Indonesian students which affect their speaking performance. Moreover, as this research is a qualitative study, direct observation is done to capture all of phenomenon happened in the speaking class in natural setting. In addition, interview is also conducted by the researcher to know what psychological factors influence their oral performance in the class. The research findings from observation and interview show that the students tend to feel anxious when performing their speaking because they are afraid of making mistakes. The feeling of fear of making mistakes, somehow related to the students’ lack of self-esteem in using English so that they often combine their speaking with their mother tongue. Psychological barriers also appear in discussion session, where in this case some students do not want to participate because they are too afraid of making mistakes, lack of self-esteem and motivation so they prefer to keep silent in the class. From the natural phenomenon happened in the speaking class, it can be concluded that psychological factors which hinder the students in performing their speaking are possibly caused by the feeling of too worried of making mistakes and the lack of self-esteem which are related to shyness and their anxiety level. By looking at this phenomenon, it is better for teacher to give their students assistance so that they can perform their English speaking better